First principles calculations of opto-electronic properties of doped blue phosphorene nanoribbons (2019)
Using first principles calculation the opto-electronic properties of blue phosphorene nanoribbons doped with carbon, silicon and sulfur atoms are studied. Zigzag and armchair edges configurations and several ribbon widths are considered. The electronic structure is analyzed and the results on band structure is used to study the optical response through the imaginary part of the dielectric function, considering light polarizations both perpendicular and parallel to the nanoribbon growth direction. The results show that carbon, silicon, and sulfur atoms in doped blue phosphorene nanoribbons induce magnetic states which appear as dispersionless energy levels above/under the Fermi level. The observed dispersionless levels in doped blue phosphorene nanoribbons suggest the presence of localized magnetic states. © 2019 Elsevier Ltd